Morphological peculiarities of revascularization of perifocal areas of brain infarction - S. I. Tertyshnyi; О. О. Voloshanska; А. М. Serheieva (Zaporozhye State Medical University, 2023)
Aim. To study pathomorphological signs of revascularization of perifocal areas of brain infarction in the dynamics of the acute period of the disease. Material and methods. Perifocal areas of brain infarction in patients who died at the 1st, 3rd, 7th, and 14th days were studied. General histopathological study was followed by 10 % ammonium silver impregnation and immunohistochemical examination using monoclonal antibodies Mo a-Hu CD34, Clone QBEnd/10 ("Thermo Fisher Scientific Inc." - USA) and Mo a-Hu CD105 Endoglin were used. clone: SN6h1 ("DAKO", Denmark). Vascular density and total cross-sectional area of vessels were studied. For the morphometric study, Videotest - Morphology 5.2.0.158 software (VideoTest LLC) was used. Statistical processing of the obtained data was carried out using the Statistica® for Windows 13.0 software. Results. According to the data of CD34 expression, from the 3rd day in the perifocal areas of brain infarction, the angiogenesis processes were increased: the density of blood vessels increased by 18.48 %, and the total cross-sectional area of vessels increased by 1.93 times. On the 7th day, the maximal vessel density and total cross-sectional area of vessels were registered in these areas; there was a vascular budding, formation of endothelial proliferates, and increased expression of CD105 on the vascular endothelium and pericytes, which indicates the active participation of the latter in angiogenesis. On the 14th day, blood vessel density and indicators of the total cross-sectional area of vessels decreased. During this period, the density of the astrocytes increased in the infarct's perifocal areas with hypertrophy of their bodies and processes. Conclusions. According to CD34 and CD105 expression data, in the perifocal areas of cerebral infarction, the processes of angiogenesis gradually increase from the 3rd day manifesting by increase in the blood vessel density and total vascular cross-sectional area, as well as in the vascular budding and the formation of endothelial proliferates. Vascular remodeling is accompanied by increased density and hypertrophy of astroglia in the perifocal areas of cerebral infarction.